Clearance of jaundice after the modified kasai’s operation predicts survival outcomes in patients with biliary atresia - Jinchanya Tamgal (2020)
© Tamgal J, et al. The aim of this study was to assess the probability of survival with native liver (SNL) and the rate of esophageal variceal bleeding (EVB) as well as their potential risk factors, in patients diagnosed with Biliary Atresia (BA), who underwent the hepaticoportoenterostomy (HPE) by retrospectively reviewing medical records between 2007 and 2016. The subjects were classified as poor outcomes if they died or a liver transplant (LT) was performed. A total of 73 cases were enrolled. The average age at HPE was 106.2 +/- 58.5 days. Poor outcome was observed in 27.4%, 54.8% survived with native liver and 17.8% were lost to follow-up. The principal cause of death was sepsis, followed by massive upper GI hemorrhage. The overall 10-year SNL was 66.8%. Only total bilirubin (TB)>3 mg/dL at 3, 6 months after HPE and presence of associated anomalies negatively affected SNL (p=0.0155, 0.0042 and 0.001, respectively). Most of the patients experienced EVB within 3 years of age, in which TB>9 mg/dL at 12 months after HPE was significantly associated with probability of the EVB outcome. Any interventions to improve jaundice clearance after HPE should be strongly pursued in order to improve outcomes in BA patients, particularly in centers where liver transplantation (LT) is not available. Surveillance esophagogastroduodenoscopy around the age of 1.5 years in patients having TB>9 mg/dL may be beneficial to identify large varices having potential fatal bleeding.